Bulk heterojunction-induced ion transport in nanochannel arrays for light-enhanced osmotic energy conversion. Issue 44 (1st November 2022) - He, Youfeng; Zhang, Liangqian; Guo, Liang; Geng, Yutong; Ren, Yan; Liu, You; Fan, Xia; Liu, Weimin; Zhai, Jin; Wang, Pengfei; Jiang, Lei
Abstract : A nanochannel array with ionic rectifying properties and excellent cation selectivity is presented. Under light irradiation, the bulk heterojunction-induced ionic current significantly increases the output power density. Abstract : Bioinspired nanochannel systems exhibiting analogous energy conversion characteristics have attracted great interest. Here, we develop a nanochannel array by modifying bilayer light-responsive molecules onto specific segments of alumina nanochannels. Based on the energy level difference between positively charged poly(3-thiophene-phenyl-tridecyl ammonium bromide) (PT2) and negatively charged cis -bis-(4, 4-dicarboxy-2, 2-bipyridine)dithiocyanato ruthenium(ii ) (N3), a bulk heterojunction is established that induces the transfer of excited electrons from donor PT2 to acceptor N3 following a "Z-scheme", which is conducive to improving ion selective transport and total transmembrane ion flux. The nanochannel array shows excellent cation selectivity and diode-like ion rectification behavior. Incorporating the enhancement of surface charge density, a record light-induced ion current change (PICC) ratio of 128% is achieved in the PT2/N3(T) nanochannel array. Owing to the synergistic effect of salinity gradient energy and light irradiation, the ion current induced by the bulk heterojunction significantly increases the output power density. The maximum improvement of power density is 79% at a load resistance of 0.7 kΩ. This work provides a new route to develop high-performance photoelectric conversion systems and integrated osmotic power generation.